Pengaruh Aplikasi Tik Tok Terhadap Minat Belajar Mahasiswa Fiikom Universitas Mercu Buana Yogyakarta Angkatan 2021 - Khotimah, Miftahul Khusnul; Adinda, Lili; Latif, Nursafika Azis Abd. (CV. ITTC INDONESIA, 2023)
Advances in technology in the field of communication and information have led to changes and human development in various aspects of life. This research is entitled